The Theme Complexity of Short Story Written by Students in Formal Operational Stage - Lestari, Arum Yuliya; Setyaningsih, Nas Haryati; Wagiran, Wagiran (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
A short story is one of the literary works. The variety of problems or events in short stories has no limits so the author has the freedom to present them. Therefore, the complexity of the themes presented by the authors is different. One of the differences is students at the junior and senior high school levels. Both enter the same cognitive development, namely the formal operational stage but have different characteristics of presenting the theme complexity. This study aimed to analyze the theme complexity of short stories written by students in the formal operational stage. This study consisted of two approaches, which were theoretical approach using an objective approach and methodological approach using a qualitative descriptive approach. The results showed that the theme complexity in short stories written by students in the operational stage was in the simple category. Based on the categories, it was found that the characteristics of short story essays for junior high school students were: (1) focusing on major themes, (2) writing short stories based on experiences or observations, (3) not presenting the theme of sexuality, and (4) rudimentary abstract thinking patterns. Then, the theme complexity in short stories written by high school students is in the medium category. According to the categories, it was found that the characteristics of short story essays for high school students were: (1) focusing on major and minor themes, (2) writing short stories based on imagination, (3) presenting the theme of sexuality, and (4) abstract thinking patterns are more perfect than junior high school level.